2008
DOI: 10.1186/1471-230x-8-56
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN expression is associated with colorectal cancer liver metastasis and poor patient survival

Abstract: Background: The tumour suppressor phosphatase and tensin homolog (PTEN) is an important negative regulator of cell-survival signaling. To evaluate the correlation between PTEN expression and clinicopathological characteristics of colorectal cancer patients with and without liver metastases, we investigated PTEN expression in primary colorectal cancer and colorectal cancer liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 33 publications
9
77
2
Order By: Relevance
“…Interestingly, one of the more sensitive lines, MDA-MB-157, expressed mutant rac (16). Loss of PTEN expression is common across many tumor types, TNBC (9), prostate (10,11), head and neck (21), colorectal cancer (22,23), and squamous lung (24), suggesting that inhibitors of PI3Kb are relevant in many diseases. Gaining insight into why PTEN WT cells are sensitive will broaden the application of these differentiated PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, one of the more sensitive lines, MDA-MB-157, expressed mutant rac (16). Loss of PTEN expression is common across many tumor types, TNBC (9), prostate (10,11), head and neck (21), colorectal cancer (22,23), and squamous lung (24), suggesting that inhibitors of PI3Kb are relevant in many diseases. Gaining insight into why PTEN WT cells are sensitive will broaden the application of these differentiated PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Given treatment with AD8186 has the potential to induce feedback through FOXO-regulated genes activating other pro-proliferative signaling pathways (21,23), intermittent pathway suppression could reduce the feedback loop-induced resistance as a result of upregulation of IGF-R-, IRS-2-, or ERB-mediated signaling as seen with AKT inhibitors (25,26,27). Moreover, when combining with other agents, being able to schedule each therapy to maximize therapeutic index is also an advantage (3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that loss of function or downregulation of PTEN resulted in tumor metastasis, and more aggressive growth behaviors of tumor, and/or poor prognostic phenotypes. 42,[49][50][51][52][53][54][55][56][57] In addition, miR-19 upregulation was observed in various cancers including lung cancer, and correlated with tumor metastasis and/or poor prognosis of cancer patients. [11][12][13][14][15]18 Given that miRNAs primarily function through inhibiting the translation of their mRNA targets, we propose that miR-19 might be a negative regulator for PTEN, which has been reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence supports that inactivation or downregulation of the tumor suppressor PTEN can trigger EMT of cancer cells, [60][61][62][63] which then promoted the invasion and metastasis of various cancers including lung cancer. 42,[49][50][51][52][53][54][55][56][57] It has been reported that PTEN negatively regulated the PI3K/ Akt pathway through the dephosphorylation of PI(3,4,5)P3, and ultimately participated in the regulation of cell cycle, proliferation, apoptosis, adhesion, and EMT during cancer progress. 63 In the present study, we found that PTEN silence through RNA interference mimicked miR-19-induced EMT, and promoted the migration and invasion of tumor cells, which were similar as the results caused by miR-19 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…4a). The tumor suppressor PTEN is a common target for inactivation in cancer, including CRC (Rahal and Simmen 2010;Sawai et al 2008;Molinari and Frattini 2013). We next evaluated whether induction of PTEN is responsible, in part, for the inhibitory effects of MET, Gen, and Lun on colonosphere formation.…”
Section: Soy Bioactive Components Alter Hct116 Cell Viability Apoptomentioning
confidence: 99%